Bacterial Biogeography of the Colon in Dogs With Chronic Inflammatory Enteropathy. Issue 2 (March 2020) - Giaretta, Paula R.; Suchodolski, Jan S.; Jergens, Albert E.; Steiner, Jörg M.; Lidbury, Jonathan A.; Cook, Audrey K.; Hanifeh, Mohsen; Spillmann, Thomas; Kilpinen, Susanne; Syrjä, Pernilla; Rech, Raquel R.
The intestinal microbiota is believed to play a role in the pathogenesis of inflammatory bowel disease in humans and chronic inflammatory enteropathy (CIE) in dogs. While most previous studies have described the gut microbiota using sequencing methods, it is fundamental to assess the spatial distribution of the bacteria for a better understanding of their relationship with the host. The microbiota in the colonic mucosa of 22 dogs with CIE and 11 control dogs was investigated using fluorescence in situ hybridization (FISH) with a universal eubacterial probe (EUB338) and specific probes for select bacterial groups. The number of total bacteria labeled with EUB338 probe was lower within the colonic crypts of dogs with CIE compared to controls. Helicobacter spp. and Akkermansia spp. were decreased on the colonic surface and in the crypts of dogs with CIE. Dogs with CIE had increased number of Escherichia coli/Shigella spp. on the colonic surface and within the crypts compared to control dogs. In conclusion, the bacterial microbiota in the colonic mucosa differed between dogs with and without CIE, with depletion of the crypt bacteria in dogs with CIE. The crypt bacterial species that was intimately associated with the host mucosa in control dogs was composed mainly of Helicobacter spp.